MENINGKATAN KEMAMPUAN OPESI PENGURANGAN DENGAN TEKNIK MEMINJAM MELALUI MEDIA BENDA ASLI BAGI ANAK TUNAGRAHITA RINGAN SEKOLAH LUAR BIASA NEGERI TANJUNGPINANG - Sri - Suwarti (Universitas Negeri Padang, 2013)
Increasing the students’ ability on substraction operation by using “borrowing of realObject medium” at SLB Negeri Tanjungpinang grade V Tuna Grahita. study is caused by the researcher faced at the tunagrahita fifth grade of SLB Negeri Tanjungpinang. There are AG, AS, FT, PT, IC, RR, RK, RZ, WN. nine (9) student which have problems at substractions, the researcher has no an appropriate technique. The aims of this research is to increase students’ ability in substractions by using ice cream stick at Tunagrahita students and the teacher as researcher of SLB NegeriTanjungpinang. The research desain is using the classroom, action research with the other teachers help. The collection data were obtained by test and observation.The research was consisted of two treatment the data of group 1 was increasing in substraction by “borrowing technique” that is IC, PT, RR, RK and WN, but the students initial RZ, FT, AS and AG, did not reached the appropriate minimum score . that’s why the research continued to do the substraction operation by “borrow technique”, the students able to do the exercise and reach score at 65.It is proven from the research that “borrowing of real object medium” able to increase the substraction on student of SLB Tunagrahita Ringan. Then borrowing technique suggested to increase the substraction achievement.